ASSESSMENT OF CRIME AND SECURITY TRENDS IN GEORGIA: FINDINGS AND RESULTS OF VICTIMIZATION SURVEYS 2010-2013 - Glonti, Georgi (European Scientific Journal, ESJ, 2014)
The author of the article analyzes the results of four waves of victimization surveys carried out in Georgia in 2010-2013 and registered crime (criminalization) data from annual reports of the Ministry of Internal Affairs of Georgia. The results of these analytical researches have acquired an additional interest in relation with the October 2012 parliamentary elections in Georgia and the reforms carried out by the new government to decriminalization of the criminal legislation and mitigation of sentences. The author analyzes the criminal effects of the general amnesty implemented by the new authorities in early 2013, which has reduced the number of inmates in Georgia's prisons by about 60%. The author also discusses indices of victimization dynamics in the past 20 years, perception of personal safety and public opinion about general criminal conditions in Georgia.